Cross-Modal Associations in Synaesthesia: Vowel Colours in the Ear of the Beholder. (April 2014) - Moos, Anja; Smith, Rachel; Miller, Sam R.; Simmons, David R.
Human speech conveys many forms of information, but for some exceptional individuals (synaesthetes), listening to speech sounds can automatically induce visual percepts such as colours. In this experiment, grapheme–colour synaesthetes and controls were asked to assign colours, or shades of grey, to different vowel sounds. We then investigated whether the acoustic content of these vowel sounds influenced participants' colour and grey-shade choices. We found that both colour and grey-shade associations varied systematically with vowel changes. The colour effect was significant for both participant groups, but significantly stronger and more consistent for synaesthetes. Because not all vowel sounds that we used are "translatable" into graphemes, we conclude that acoustic–phonetic influences co-exist with established graphemic influences in the cross-modal correspondences of both synaesthetes and non-synaesthetes.